2017
DOI: 10.1088/1741-2552/aa814d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical fatigue resistance of an implantable branched lead system for a distributed set of longitudinal intrafascicular electrodes

Abstract: Objective A neural interface system has been developed that consists of an implantable stimulator/recorder can with a 15-electrode lead that trifurcates into three bundles of five individual wire longitudinal intrafascicular electrodes. This work evaluated the mechanical fatigue resistance of the branched lead and distributed electrode system under conditions designed to mimic anticipated strain profiles that would be observed after implantation in the human upper arm. Approach Custom test setups and procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…A major problem with chronic neurostimulation of peripheral nerve for purposes of neural interfacing is that of lead wires tugging on microelectrodes penetrating into the body of a nerve. This becomes a more severe problem when large numbers of wires are used for advanced multichannel neural interface systems needed for both sensory and motor control of prosthetics [ 5 ]. Such systems require more channels than can be provided by most nerve cuff systems and need to contact or stimulate nerves lying deeper at the fascicular and subfasicular level.…”
Section: Introductionmentioning
confidence: 99%
“…A major problem with chronic neurostimulation of peripheral nerve for purposes of neural interfacing is that of lead wires tugging on microelectrodes penetrating into the body of a nerve. This becomes a more severe problem when large numbers of wires are used for advanced multichannel neural interface systems needed for both sensory and motor control of prosthetics [ 5 ]. Such systems require more channels than can be provided by most nerve cuff systems and need to contact or stimulate nerves lying deeper at the fascicular and subfasicular level.…”
Section: Introductionmentioning
confidence: 99%
“…Each group of LIFEs can be implanted Fig. 6 Several forms of intrafascicular electrodes a The intrafascicular drawing of LIFE [84] b Schematic of the TIME [8] c Illustration of the SELINE [85] d USEA [86] in different nerves, and each LIFE can be implanted in different fascicles or in the separate areas of the same fascicle [94]. A 6-month rat study showed electrode breakage in a small percent of the electrodes leading to failure [95].…”
Section: Intra-fascicular Electrodesmentioning
confidence: 99%
“…for cardiac pacemakers (123) and cochlear implants: (124, 125)), and these studies are typically performed under accelerated conditions to achieve high cycle numbers (i.e. long equivalent implant years) over months of testing (122) or are run to cable failure (121).…”
Section: In Vitro Evaluation Of Device Safety and Reliabilitymentioning
confidence: 99%